Debating the applicability of Gagné`s talent development model in the sport domain - MacDonald, D. J. (Talent Development & Excellence, 2011)
Taken together, the constructs of relative age and birthplace demonstrate that fostering talent in youth is a highly complex issue and that multi athletic development. This appears to be inconsistent with the vision of talent development put forth by Gagné which suggests that special attention should be given to certain individuals, regardless of the other factors of the other factors outlined above. Although it is possible that the DMGT model is applicable in other domains, we may in fact be bypassing a significant number of talented individuals in youth if we focus our attention on select groups of young age. As outlined by Vaeyens et, youth development programs are mostly ineffective, which suggests that we need to expand the opportunities we provide to youth rather than restrict such opportunities. If the goal of sport is to develop high-level athletes, then maximizing the development programs, rather than minimizing the number of youth in such programs, will increase the probability of identifying talented individuals.